Catalogue of New Zealand land, freshwater and estuarine molluscan taxa named by Frederick Wollaston Hutton between 1879 and 1904 - Brook, Fred J.; Kennedy, Martyn; King, Tania M.; Ridden, Johnathon; Shaw, Matthew D.; Spencer, Hamish G. (Zootaxa, 2020)
Details are provided on 16 land snail genera, eight freshwater molluscan species, one estuarine species, 47 land snail species and varieties from New Zealand, and a further three land snail species putatively from New Zealand, which were described by Frederick Wollaston Hutton between 1879 and 1904. Original primary type material of 54 species was located during the present study. Lectotypes are designated for: Amphidoxa cornea Hutton, 1882, Amphidoxa jacquenetta Hutton, 1883, Amphidoxa perdita Hutton, 1883, Charopa cassandra Hutton, 1883, Cyclotus charmian Hutton, 1883, Fruticicola adriana Hutton, 1883, Gerontia cordelia Hutton, 1883, Gerontia pantherina Hutton, 1882, Microphysa pumila Hutton, 1882, Patula jessica Hutton, 1883, Patula lucetta Hutton, 1884, Patula sylvia Hutton, 1883, Patula tapirina Hutton, 1882, Pfeifferia cressida Hutton, 1883, Phrixgnathus celia Hutton, 1883, Phrixgnathus haasti Hutton, 1883, Phrixgnathus marginatus Hutton, 1882, Phrixgnathus phrynia Hutton, 1883, Rhytida australis Hutton, 1882, Strobila leiodon Hutton, 1882, Thalassia propinqua Hutton, 1882, Therasia thaisa Hutton, 1883, Therasia valeria Hutton, 1883 and Zonites helmsii Hutton, 1882. A neotype is designated for Rhytida citrina Hutton, 1882. Primary type material of the following taxa is figured herein for the first time: Amphidoxa lavinia Hutton, 1883, Cyclotus charmian Hutton, 1883, Fruticicola adriana Hutton, 1883, Leptopoma pannosa Hutton, 1882, Patula lucetta Hutton, 1884, Patula sylvia Hutton, 1883, Patula tapirina Hutton, 1882, Phacussa helmsi var. maculata Hutton, 1884, Phrixgnathus ariel Hutton, 1883, Phrixgnathus celia Hutton, 1883, Rhytida australis Hutton, 1882, Rissoa vana Hutton, 1873, Testacella vagans Hutton, 1882, Trochomorpha hermia Hutton, 1883 and Zonites helmsii Hutton, 1882. New taxonomic combinations introduced herein include Phacussa lucetta (Hutton, 1884) and Therasia propinqua (Hutton, 1882). Amphidoxa lavinia Hutton, 1883, Charopa cassandra Hutton, 1883, Patula timandra Hutton, 1883 and Trochomorpha hermia Hutton, 1883 are treated as junior synonyms of Tasmaphena sinclairii (Pfeiffer, 1846), Phacussa fulminata (Hutton, 1882), Fectola infecta (Reeve, 1852) and Advena campbellii (Gray, 1834), respectively.